Pharmacokinetic Evaluation of Eltrombopag in ITP Pediatric Patients - Dionisi, Marco; Cairoli, Sara; Simeoli, Raffaele; De Gennaro, Francesca; Paganelli, Valeria; Carta, Roberto; Rossi, Francesca; Dionisi-Vici, Carlo; Palumbo, Giuseppe; Goffredo, Bianca Maria (Frontiers in Pharmacology, 2021)
Background: Eltrombopag (EPAG) is an oral thrombopoietin receptor agonist, approved for refractory primary immune thrombocytopenia (ITP) in paediatric patients. In two pediatric RCTs, EPAG led to an improvement of platelet counts and a reduction in bleeding severity. However, a significant portion of paediatric patients did not achieve the primary endpoints. We performed a pharmacokinetic evaluation of EPAG in paediatric patients with refractory ITP. Methods: Outpatients aged from 1 to 17 years, affected by ITP and refractory to first line treatment were enrolled for pharmacokinetic assessment. Analysis of drug plasma concentration was performed by LC-MS/MS platform. Non-compartmental and statistical subgroup analyses were carried out using the R package ncappc. Results: Among thirty-six patients eligible for PK analysis, the median dose of EPAG given once daily was 50 mg. EPAG peak occurs between 2 and 4 hours with a population Cmax and AUC 0-24 geo-mean of 23,38 µg/mL and 275,4 µg*h/mL. The pharmacokinetic profile of EPAG did not show a dose proportionality. Female patients showed a statistically significant increase of dose-normalized exposure parameters, increasing by 110% and 123% for Cmax and AUC 0-24 respectively when compared to males. Patients aged 1-5 years showed values increased by more than 100% considering both exposure parameters, compared to older children. Furthermore, patients presenting complete response (83%), showed augmented EPAG exposure parameters compared to subjects with partial or no response. Conclusion: These data highlight the need to further explore variability of EPAG exposure and its pharmacokinetic/pharmacodynamic profile in paediatric patients also in a real-life setting.